Idiopathic Granulomatous Mastitis: An Autoimmune Disease? - Fatih Altintoprak; Engin Karakece; Taner Kivilcim; Enis Dikicier; Guner Cakmak; Fehmi Celebi; Ihsan Hakkı Ciftci (The Scientific World Journal)
Purpose. This study aimed to investigate the autoimmune basis of idiopathic granulomatous mastitis (IGM) by determining the anti-nuclear antibody (ANA) and extractable nuclear antigen (ENA) levels of patients diagnosed with IGM. Material and Methods. Twenty-six IGM patients were evaluated. Serum samples were analyzed for autoantibodies by indirect immunofluorescence (IIF) using a substrate kit that induced fluorescein-conjugated goat antibodies to human immunoglobulin G (IgG). IIF patterns were read at serum dilutions of 1 : 40 and 1 : 100 for ANA positivity. Using the immunoblot technique, the sera of patients were assayed at dilutions of 1 : 40 and 1 : 100 for human autoantibodies of the IgG class to 15 lines of highly purified ENAs. Results. In the IIF studies for ANA, positivity was identified for four different patterns in the 1 : 40 diluted preparations, for three different patients in the 1 : 100 diluted preparations and only one pattern was identified at the 1 : 320 dilution. In the ENA studies, positivity was identified for four different pattern in the 1 : 40 dilution, and only one pattern was identified at the 1 : 100 dilution. Conclusion. This study was not able to support the eventual existence of an autoimmune basis for IGM.